Characterization of the humanized FRG mouse model and development of an AAV-LK03 variant with improved liver lobular biodistribution - Cabanes-Creus, Marti; Navarro, Renina Gale; Liao, Sophia H.Y.; Scott, Suzanne; Carlessi, Rodrigo; Roca-Pinilla, Ramon; Knight, Maddison; Baltazar, Grober; Zhu, Erhua; Jones, Matthew; Denisenko, Elena; Forrest, Alistair R.R.; et al. (Molecular therapy. Methods & clinical development, 2023)
Recent clinical successes have intensified interest in using adeno-associated virus (AAV) vectors for therapeutic gene delivery. The liver is a key clinical target, given its critical physiological functions and involvement in a wide range of genetic diseases. In the present study, we first investigated the validity of a liver xenograft mouse model repopulated with primary hepatocytes using single-nucleus RNA sequencing (sn-RNA-seq) by studying the transcriptomic profile of human hepatocytes pre- and post-engraftment. Complementary immunofluorescence analyses performed in highly engrafted animals confirmed that the human hepatocytes organize and present appropriate patterns of zone-dependent enzyme expression in this model. Next, we tested a set of rationally designed HSPG de-targeted AAV-LK03 variants for relative transduction performance in human hepatocytes. We used immunofluorescence, next-generation sequencing, and single-nucleus transcriptomics data from highly engrafted FRG mice to demonstrate that the optimally HSPG de-targeted AAV-LK03 displayed a significantly improved lobular transduction profile in this model. [Display omitted] Using single-nucleus RNA sequencing and complementary immunofluorescence analyses, the authors confirmed that human hepatocytes engrafted in xenograft mice organize and present appropriate patterns of liver-zone-dependent enzyme expression. Having confirmed this, the authors successfully performed targeted bioengineering of a clinical AAV variant, AAV-LK03, to improve its lobular transduction profile.